The New Politics of Adultery - Cossman, Brenda (Columbia Journal of Gender and Law, 2006)
Adultery is nothing new. Nor are social sanctions against it. But there is something new in the contemporary cultural politics of adultery, which begins with an ever-expanding definition of infidelity. Once restricted to “natural heterosexual intercourse,” infidelity now extends to a variety of sexual practices. Indeed, these days, infidelity can occur without sexual contact at all. Computer sex, telephone sex, and email flirtations are all included within the ambit of adulterous relationships that violate the marital relationship. As the definition of infidelity expands, so do its practitioners. In several recent exposes of “the new infidelity,” women have increasingly been shown to be equal opportunity cheaters. This expansion of infidelity and infidels has produced a new crisis of adultery; a virtual adultery epidemic has swept the nation. Crises, in turn, require intervention. The “epidemic” has produced a new emphasis on both prevention and treatment. The first line of protection against adultery is a prevention strategy, based on identifying and minimizing risks. This approach involves a politics of self-discipline, of individuals recognizing and taking responsibility for managing the risks to their relationships.